(untitled) (Faridpur Medical College Journal, 2020)
Preeclampsia is one of the most important pregnancy disorder, diagnosed with hypertension and proteinuria. It is the leading cause of fetal and maternal morbidity and mortality. This cross-sectional study was conducted in 100 pregnant women, of them, 50 were diagnosed cases of preeclampsia and 50 were normal pregnant women attended in the Gynaecology and Obstetrics department of Dhaka Medical College Hospital, Dhaka, during July 2016 to June 2017. Five ml fasting blood sample was collected and was analysed for triglyceride using standard enzymatic method. Mean value of triglyceride was compared between two groups by student unpaired t-test and the triglyceride level was correlated with systolic, diastolic blood pressure and urine albumin in preeclamptic patient was correlated by Pearson’s correlation coefficient test. A p-value was considered to be statistically significant at 0.05 at 95% confidence interval. Statistically significant difference of serum triglyceride level was found in preeclamptic women and normal pregnant women (p<0.05). The level was 248.90±31.36 mg/dl in preeclampsia and 197.00±27.04 mg/dl in normal pregnant women respectively. Serum triglyceride was positively correlated with systolic, diastolic blood pressure and urine albumin in preeclamptic women. Faridpur Med. Coll. J. Jul 2019;14(2): 82-85